Trends in Electric Vehicle Motor Power: A Comparative Study on Performance and Efficiency - Orhan, Ahmet; Unal, Sencer; Akbal, Ayhan; Kıvanç,; Kayaoğlu, Murat Murat; Hilal, (My University, 2025)
Electric vehicles (EVs) have increasingly become central to modern transportation systems due to their advantages in environmental sustainability and energy efficiency. In this development process, electric drive motors play a decisive role in key criteria such as performance, range, energy consumption, and production costs. In this study, three primary motor types commonly used in electric vehicles the Wound Rotor Synchronous Motor (WRSM), Permanent Magnet Synchronous Motor (PMSM), and Induction Motor (IM) are evaluated in a multidimensional manner in terms of their technical performance, energy efficiency, and application segments. Comparative analyses reveal that PMSM motors, in particular, provide an optimal power-to-weight ratio for mid-range vehicles due to their high torque generation and low energy consumption. The compact structure and high efficiency levels of these motors have made them the standard choice for many manufacturers today. On the other hand, WRSM motors offer a strong alternative for long-term sustainability goals by eliminating dependence on rare-earth elements and providing field weakening capability. The high-temperature tolerance, low maintenance requirements, and wide speed range operating capability of WRSM motors indicate their potential for broader adoption in the future. Segment-based evaluations have determined that vehicles in the economic class offer longer range per unit of energy due to lower weight and limited power requirements, representing a significant advantage for compact electric vehicles intended for urban use in terms of energy savings. Conversely, luxury and high-performance segment vehicles demonstrate higher energy consumption despite larger battery capacities; in these segments, factors such as acceleration, traction power, and driving comfort are prioritized over efficiency. The general findings indicate that motor power plays a critical role not only in performance but also in energy consumption, range capacity, and segment-based product positioning. Furthermore, the increasing research and development efforts on alternative motor architectures such as WRSM suggest that these motors may become more attractive both economically and environmentally in the future. In this context, it is recommended that interdisciplinary research on motor technologies be intensified in order to achieve sustainable electric transportation objectives.
Keywords: Electric Vehicles; Induction Motor; Permanent Magnet Synchronous Motor; Brushless DC Motor; Wound Rotor Synchronous Motor